Smart Grid Asset Monitoring and Management through Blockchain Technology (International Journal of Food and Nutritional Sciences, 2022)
The smart grid is an electrical network built on digital technology that transmits power tousers in both directions. The system enables monitoring, analysis, control, andcommunication throughout the supply chain to enhance efficiency, lower energy usage andexpenses, and increase the supply chain’s transparency and dependability. Here, we used anumber of IOT devices to obtain meter readings and related information and send them tothe control center for processing the data and adding them to the blockchain ledgers.During the transmission of data from IoT devices to the control center, the data can betampered. This can be prevented using a blockchain. Identification and communication willalso be implemented to maintain confidentiality and reliability which can be attainedthrough ABE. We will outline a architecture for a blockchain-based platform for managingsmart grids that include tamper-proof registration and energy data metering. We used theblockchain to manage transactions in the smart grid